2018
DOI: 10.1002/jbm.b.34193
|View full text |Cite
|
Sign up to set email alerts
|

Large scale segmental bone defect healing through the combined delivery of VEGF and BMP‐2 from biofunctionalized cortical allografts

Abstract: Large scale cortical allografts suffer from poor incorporation and healing and often end in graft failure 5-10 years after implantation. To reduce these failures we have developed a growth-factor loaded cortical allograft capable of delivering one or two factors with a degree of temporal control and precision that permits the early release of one growth factor followed by the later and more sustained release of the other. We have loaded vascular endothelial growth factor (VEGF) and bone morphogenetic protein-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 42 publications
(67 reference statements)
0
23
0
Order By: Relevance
“…It is notable that approaches to enhance vascularity are now at the forefront of tissue engineering strategies to repair large bone defects, as it is assumed that poor vascularization may be one factor associated with poor healing of large bone defects. Particularly co‐delivery of angiogenic and osteogenic factors is highly topical . As this field moves forward it will be essential to examine potential bone regeneration therapeutics in vascular compromised models.…”
Section: Comorbidities Influencing Fracture Healingmentioning
confidence: 99%
“…It is notable that approaches to enhance vascularity are now at the forefront of tissue engineering strategies to repair large bone defects, as it is assumed that poor vascularization may be one factor associated with poor healing of large bone defects. Particularly co‐delivery of angiogenic and osteogenic factors is highly topical . As this field moves forward it will be essential to examine potential bone regeneration therapeutics in vascular compromised models.…”
Section: Comorbidities Influencing Fracture Healingmentioning
confidence: 99%
“…The BMP-2 + BCP results at the end of 4 weeks were better than the BMP-2 + FGF-2 + BCP results, whereas the BMP-2 + FGF-2 + BCP group results were better at the end of 8 weeks [11]. Similarly, Sharmin et al reported that the combination of vascular endothelial growth factor and BMP was superior to BMP-2 alone [60].…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies reported that co-delivery of VEGF with BMP-2 enhanced the bone healing effect of BMP-2 by interacting with BMP-2 and regulating its biological activity. [25,[32][33][34][35]In particular, sequential delivery of VEGF followed by BMP-2 improved bone healing compared to simultaneous VEGF and BMP-2 delivery. [25,35] In contrast, other studies demonstrated insignificant effects of VEGF and BMP-2 on bone healing.…”
Section: Smart Delivery System Enables Tunable Delivery Of Multiple Growth Factorsmentioning
confidence: 99%